Passive Suicidal Ideation and Community Mental Health Resources in South Africa - Collins, Pamela Y. (Community Ment Health J, 2016)
South African communities continue to experience elevated incidence and prevalence of HIV infection. Passive suicidal ideation (PSI) may be one expression of distress in high prevalence communities. We report the prevalence of PSI and examine the relationship between PSI and participation in community organizations in a semi-rural sample of South African adults (N = 594). The prevalence of PSI in the 2 weeks prior to the interview was 9.1 %. Members of burial societies (X(2) = 7.34; p = 0.01) and stokvels (X(2) = 4.1; p = 0.04) (community-based savings groups) reported significantly less PSI compared to other respondents. Using a multivariate model adjusted for demographic characteristics, psychological distress, and socioeconomic status, we found lower odds of reporting PSI for members of burial societies (OR 0.48, CI 0.25 –0.91). Participation in community organizations that provide contextually salient resources in settings with high levels of distress may be a resource for mental health.